2009
DOI: 10.1002/jssc.200900071
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic methods for separation of nanoparticles

Abstract: This article reviews progress in the application of electrophoretic techniques for the separation of nanoparticles. Numerous types of nanoparticles have recently been synthesised and integrated into different products and procedures. Consequently, analytical methods for the efficient characterisation of nanoparticles are now required. Several studies have revealed that gel electrophoresis can readily be used for separating nanoparticles according to their size or shape. However, many other studies focused on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 143 publications
2
119
0
Order By: Relevance
“…Gel electrophoresis and capillary electrophoresis, which are the two electrophoretic techniques most commonly used for separation and characterization of nanoparticles [168][169][170] will be considered. Whereas most of the work with electrophoretic techniques has been devoted to the separation and characterization of nanoparticles according to size, shape and surface functionalization, using electrophoresis as diagnostic tool, the number of applications to real-world samples is still scarce.…”
Section: Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…Gel electrophoresis and capillary electrophoresis, which are the two electrophoretic techniques most commonly used for separation and characterization of nanoparticles [168][169][170] will be considered. Whereas most of the work with electrophoretic techniques has been devoted to the separation and characterization of nanoparticles according to size, shape and surface functionalization, using electrophoresis as diagnostic tool, the number of applications to real-world samples is still scarce.…”
Section: Electrophoresismentioning
confidence: 99%
“…In this sense, bioconjugated quantum dots [175,176] and protein-nanoparticle interactions [177] are commonly studied by CE. Although metal and metal oxide nanoparticles have been separated by using different inorganic buffers as electrolytes, the addition of ionic surfactants appears to be the most convenient mode for separation of metallic nanoparticles [168][169][170]. For instance, Liu et al [178] demonstrated that addition of sodium dodecyl sulphate to the background electrolyte improved the size separation of Au NPs, because of the charge of the NPs is then related to the number of molecules of surfactant adsorbed, which acts as a sort of in situ derivatizing agent.…”
Section: Electrophoresismentioning
confidence: 99%
“…Therefore conventional or microfluidic CE is a good alternative for characterization of colloids and nanomaterials. Review articles focusing on electrophoretic separation of nanoparticles has been published in 2004 by Rodriguez and Armstrong [37], later by Surugau and Urban [38], Pyell [39], Lopez-Lorente et al [40], and in 2017 by Aleksenko et al [41]. Microfluidic format used in nanoparticle separation was reviewed by Salafi et al [42].…”
Section: Capillary Electrophoresis For Analysis Of Nanomaterialsmentioning
confidence: 99%
“…FFF includes flow field-flow fractionation (FFFF), sedimentation field-flow fractionation, and thermal fieldflow fractionation (Gimbert et al, 2005;Baalousha et al, 2006;Hassellöv et al, 2008;Plathe et al, 2010;Baalousha et al, 2011;von der Kammer et al, 2011). Other important methods are centrifugation and ultracentrifugation (Bootz et al, 2004;Hassellöv et al, 2008), size-exclusion chromatography (SEC) (Weinberg et al, 2011), hydrodynamic chromatography (Tiede et al, 2010), capillary electrophoresis (CE) (Celiz et al, 2011), gel electrophoresis (Surugau and Urban, 2009), isoelectric focusing (Howard, 2010), manipulation between solvent phases such as cloud point extraction (Howard, 2010;Liu et al, 2012), and photophoretic velocimetry (Helmbrecht et al, 2011). Most of these fractionation techniques can be coupled with detectors that can trace the separated particles online.…”
Section: Pretreatment and Particle Fractionationrelated Techniquesmentioning
confidence: 99%